2003
DOI: 10.1161/01.cir.0000077064.67790.5b
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regurgitation in Branch Pulmonary Arteries After Repair of Tetralogy of Fallot

Abstract: Background-The importance of pulmonary regurgitation (PR) after repair of tetralogy of Fallot (TOF) is increasingly recognized, but little is known regarding its underlying mechanisms. This phase-contrast cine magnetic resonance (PC MR) study was performed to evaluate the relative contribution of each lung to total regurgitant volume. Methods and Results-Twenty-two patients with significant PR underwent a PC MR 3 to 16 years after repair of TOF.Regurgitant fraction of the main pulmonary artery was 39Ϯ10%. Regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 29 publications
5
14
0
Order By: Relevance
“…Further delineation of regurgitation in the branch pulmonary arteries was performed by Kang et al . [29] Their phase contrast cine MR comparison of regurgitation showed greater regurgitation fractions in the left pulmonary artery compared to the right, consistent with Figure 3.…”
Section: Introductionsupporting
confidence: 72%
“…Further delineation of regurgitation in the branch pulmonary arteries was performed by Kang et al . [29] Their phase contrast cine MR comparison of regurgitation showed greater regurgitation fractions in the left pulmonary artery compared to the right, consistent with Figure 3.…”
Section: Introductionsupporting
confidence: 72%
“…Since it provides accurate quantitative information on biventricular size and function, blood flow measurements, myocardial viability, and cardiovascular anatomy, in many centers CMR has become the preferred method of noninvasive imaging in patients with repaired TOF [10,45,50,54,97,110-113]. At Children's Hospital Boston, postoperative TOF is the most common diagnosis in patients referred for CMR, accounting for ~23% of patients.…”
Section: Role Of Cmrmentioning
confidence: 99%
“…Phase contrast magnetic resonance (PC-MR) technology is an established noninvasive technique to estimate blood flow in the vessels and has been used to investigate the PR phenomena in repaired TOF patients. According to Kang et al's [1] PC-MR measurements of repaired TOF, it was found that the regurgitation fraction (RF, i.e., backward flow volume/forward flow volume) of PR in left pulmonary artery (LPA) is higher than right pulmonary artery (RPA) in repaired TOF. The reason causing this discrepancy of RF is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [1] discussed the difference of PR between left and right pulmonary arteries from PC-MRI measurements for 22 patients after repaired TOF surgery. They found that the regurgitant fraction in LPA is greater than that in RPA and MPA in most of repaired TOF patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation